Cerebrospinal Fluid Cytokines in Patients with Neurosyphilis: The Significance of Interleukin-10 for the Disease. (5th October 2020) - Li, Wurong; Wu, Wenqing; Chang, Haoxiao; Jiang, Meijuan; Gao, Junhua; Xu, Yun; Xu, Dongmei; Yin, Linlin; Zhang, Xinghu
Abstract : The aim of this study was to examine the cerebrospinal fluid (CSF) concentrations of proinflammatory and anti-inflammatory cytokines in neurosyphilis (NS), analyze the differences between asymptomatic NS (ANS) and symptomatic NS (SNS), and explore the diagnostic value of these cytokines. We enrolled 45 patients with a diagnosis of NS, including 18 patients with ANS and 27 patients with SNS, whose cerebrospinal fluid (CSF) samples were collected before penicillin therapy. Twelve patients with syphilis but non-NS (NNS) were also included. We measured the CSF levels of interleukin- (IL-) 1 β, IL-4, IL-6, IL-10, IL-17A, IL-21, and tumor necrosis factor- (TNF-) α ; the CSF levels of the microglial activation marker soluble triggering receptor expressed on myeloid cells 2 (sTREM2); and the CSF levels of the neuronal injury marker neurofilament light proteins (NFL) using the human cytokine multiplex assay or ELISA. Of the measured cytokines in the CSF, only IL-10 levels were significantly increased in NS patients compared to NNS patients (p < 0.001 ). In a subgroup analysis, the CSF levels of IL-10 were significantly elevated in SNS patients compared to ANS and NNS patients (p = 0.024 and p < 0.001, respectively). The CSF IL-10 levels had a significant correlation with the markers of microglial activation and neuronal injury, and they also correlated with CSF rapid plasma reagin (RPR) titer, CSF white blood cell (WBC) count, and CSF protein concentration. The areas under the ROC curve (AUC) of CSF IL-10 in the diagnosis of NS and ANS were 0.920 and 0.891, respectively. The corresponding sensitivities/specificities were 86.7%/91.7% and 83.3%/91.7%, respectively. Therefore, the excessive production of IL-10 might facilitate bacterial persistent infection, play an important role in the pathogenesis of NS, and associate with the progression of the disease. CSF IL-10 concentration had a useful value in the diagnosis of NS, especially in ANS.